Nanoparticles as Endodontic Irrigation: An Update Overview - Eman M. Yahya; Raghad S. Jamel (Al-Rafidain Dental Journal, 2023)
Aims: The purpose of this study is to provide a complete overview of the current scientific information on the use of nanoparticles in endodontic irrigation. The complicated structure of the root canals makes thorough cleaning and disinfection difficult. The removal of infection from the root canal system is the primary goal of root canal treatment. Irrigation is the only way to sterilize inaccessible anatomic irregularities. Because of the nanoparticles ultra-smallsizes, big surface area/mass ratio, and enhanced chemical reactivity, applying them with irrigants improves disinfection efficiency. Conclusion: The use of nanoparticles in irrigation can improve the antibiofilm efficacy of endodontic treatment particularly against chronic endodontic infections like E. faecalis. Many more researches are required to identify the best nanoparticles for use in root canal irrigation, which is still in the works